2018
DOI: 10.1101/361667
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Most sleep does not serve a vital function. Evidence from Drosophila melanogaster

Abstract: Sleep appears to be a universally conserved phenomenon among the animal kingdom but whether this striking evolutionary conservation underlies a basic vital function is still an open question.Using novel technologies, we conducted an unprecedentedly detailed high-throughput analysis of sleep in the fruit fly Drosophila melanogaster, coupled with a life-long chronic and specific sleep restriction. Our results show that some wild-type flies are virtually sleepless in baseline conditions and that complete, forced … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 52 publications
1
24
0
Order By: Relevance
“…Consistent with P(Wake) driving the expression of rebound sleep, the total amount of rebound is more strongly correlated with change in P(Wake) (R = −0.97, P < 0.0001) than change in P(Doze) (R = 0.19, P = 0.06), and the effect size of the change in P(Wake) is larger than the effect size of P(Doze) (Cohen's d = −1.46 and 0.81, respectively) (32). One implication of this result is that the magnitude of rebound sleep is a flawed measure of sleep homeostasis, consistent with recent reports (21). Interestingly, P(Doze) also appears to be regulated by "wake pressure" in addition to sleep pressure.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…Consistent with P(Wake) driving the expression of rebound sleep, the total amount of rebound is more strongly correlated with change in P(Wake) (R = −0.97, P < 0.0001) than change in P(Doze) (R = 0.19, P = 0.06), and the effect size of the change in P(Wake) is larger than the effect size of P(Doze) (Cohen's d = −1.46 and 0.81, respectively) (32). One implication of this result is that the magnitude of rebound sleep is a flawed measure of sleep homeostasis, consistent with recent reports (21). Interestingly, P(Doze) also appears to be regulated by "wake pressure" in addition to sleep pressure.…”
Section: Resultssupporting
confidence: 86%
“…S2). Previous research has found that each fly has an idiosyncratic preference for a range of behaviors, including total daily sleep (20,21). We find that P(Wake) and P(Doze) are similarly idiosyncratic, but the population mean is a reasonable estimate of the central tendency of the P(Wake) and P(Doze) distributions for WT flies (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…Alternatively, it may be that the two-process model simply does not reflect regulation of sleep pressure in Drosophila . Recent evidence suggests that sleep pressure in flies is primarily regulated by the clock rather than by sleep debt (Geissmann et al 2019). The lack of agreement between model and empirical results suggests the need for a revised and more broadly-based model of sleep drives.…”
Section: Discusssionmentioning
confidence: 99%
“…Animals with much smaller nervous systems, such as insects, also sleep (1)(2)(3)(4)(5)(6)(7)(8). Mechanisms that control sleep include circadian circuits, which underlie daily rhythms of sleep and other biological variables (9).…”
mentioning
confidence: 99%